2021
DOI: 10.1002/prot.26293
|View full text |Cite
|
Sign up to set email alerts
|

Identification, analysis, and modeling of the YUCCA protein family genome‐wide in Coffea canephora

Abstract: Auxin is involved in almost every aspect of plant growth and development, from embryogenesis to senescence. Indole-3-acetic acid (IAA) is the main known natural auxin that is synthesized by enzymes tryptophan aminotransferase of arabidopsis (TAA) and YUCCA (YUC) of the flavin-containing monooxygenases family (FMO) from one of the tryptophan-dependent pathways. Genome-wide identification and comprehensive analysis of the YUC-protein family have been conducted in Coffea canephora in the present study. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…IAA is synthesized by the enzymes tryptophan aminotransferase of Arabidopsis (TAA) and YUCCA (YUC) from one of the tryptophandependent pathways. Uc-Chuc et al [27] identi ed 10 members of the CcYUC gene family in C. canephora. Quintana-Escobar et al [28] showed differences in the concentration of auxin homeostasis proteins in C. arabica, with a more signi cant accumulation of ABCs, GH3.17, UGT75C1 and IBR1 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…IAA is synthesized by the enzymes tryptophan aminotransferase of Arabidopsis (TAA) and YUCCA (YUC) from one of the tryptophandependent pathways. Uc-Chuc et al [27] identi ed 10 members of the CcYUC gene family in C. canephora. Quintana-Escobar et al [28] showed differences in the concentration of auxin homeostasis proteins in C. arabica, with a more signi cant accumulation of ABCs, GH3.17, UGT75C1 and IBR1 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…There are 11 CsYUC proteins that contain the NAD_binding_8 domain, including CsYUC2.1, -2.2, -6, -11.1, -11.2, -11.4, -11.5, -11.6, -11.7, -11.8, and -11.9. Previous reports have suggested that the FMO domain can bind FAD and NADPH, and these are its most prominent characteristics [8]. Thus, the FMO domain, acting as the FAD-and NADPHbinding sites, is essential for YUC enzymatic activities [3].…”
Section: Gene Structure and Conserved Domain Analysis Of Csyuc Genesmentioning
confidence: 98%
“…IAA is the richest and most predominant auxin in plants [5][6][7]. In plants, the central IAA biosynthetic pathway is the indole-3-pyruvic acid (IPyA) pathway (i.e., TAA/YUC pathway), which is essential for almost all the major developmental processes in plants [7][8][9]. YUCCA (YUC) enzymes catalyze the rate-limiting second step in the TAA/YUC pathway, which converts IPyA into IAA, and belong to a class of flavin-containing monooxygenases (FMOs) [1,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Auxins are involved in the regulation of plant growth and development (Davies, 2010; Ge et al., 2019; Ross & Reid, 2010). Recently, a lot of information on the tryptamine pathway of IAA biosynthesis has been obtained because of the identification of flavin monooxygenases (YUC family) from Arabidopsis and maize, which have been demonstrated to catalyze the N ‐hydroxylation of tryptamine (Lu et al., 2023; Uc‐Chuc et al., 2022; Yamamoto et al., 2007). The flavin monooxygenase FZY is a YUC homolog from tomato and an important enzyme involved in a rate‐limiting step of IAA biosynthesis (Tivendale et al., 2010).…”
Section: Introductionmentioning
confidence: 99%